Avaliação da ocorrência de danos cromossômicos, apoptose e necrose em células esfoliadas da mucosa oral de usuários de esteróides anabolizantes androgênicos - Souza, Jeanderson Pereira (2013)
Exposure to genotoxic agents induces changes in the DNA molecule to commit that genes involved with the repair mechanisms and the control of cell proliferation and differentiation pathways or genes associated with apoptosis can lead to cancer development. Among the many chemicals that have been identified as mutagenic action, include the Androgenic Steroids (AAS), hormones widely used in the search for improved physical performance and increased muscle mass. Objective: In this context, the aim of the development of this study was to evaluate the potential of androgenic anabolic steroid nandrolone decanoate, testosterone propionate and testosterone cypionate to induce chromosome damage, apoptosis and necrosis, using the micronucleus test in exfoliated cells from the oral mucosa of users of AAS with a view to its application as a tool in cancer prevention. Method: The study sample consisted of 55 volunteers, male, divided into two (02) groups, matched for age: 25 subjects (G1) users of nandrolone decanoate, testosterone propionate and testosterone cypionate (alone or simultaneously ) and 30 subjects in the control group (G2). The collection methodology and cytological analysis followed the protocol of Tolbert et al. (1992) and Thomas et al. (2009), which includes, in addition to micronuclei, the computation of degenerative nuclear changes indicative of apoptosis (cariorréxis, condensed chromatin and pyknosis) and necrosis (karyolysis, cariorréxis, condensed chromatin and pyknosis). Statistical analysis of the endpoints analyzed (micronucleus, cariorréxis, condensed chromatin, karyolysis, pyknosis and broken eggs) was performed using the conditional test to compare proportions in situations of rare events. Results: Statistical analysis revealed no significant difference in the occurrence of micronuclei, karyolysis and broken eggs between groups. The occurrence of apoptosis was significantly greater in cells from control individuals. Conclusion: The results show inhibition of apoptosis induced by EAA, suggesting that the described association between the use of these substances and the carcinogenic process can be permeated by this mechanism.